Structure-based design and synthesis of (E)-l-(s-pheny1)-N-(4-(2,2,4-trimethy1–2,3-dihydro-lH-benzo[b][l,4]diazepin-l-yl)phenyl)methanimine motifs as antimicrobial and anti-tubercular agents - Olayinka O. Ajani; Mfonobong L. Ekpene; Gbolahan O. Oduselu; Olayinka O. Tolu-Bolaji; Oluwaseun Ejilude (Scientific African)
Benzodiazepines' chemistry and synthesis as heterocyclic compounds have recently attracted a lot of attention, due to their extensive biological diversity in drug design and potential for usage in agrochemicals. Eco-friendly and highly efficient method was herein reported for the synthesis of a new series of Schiff base of benzodiazepine derivatives 3a-l using microwave-assisted approach. Firstly, 2,2,4-trimethy1–2,3-dihydro-lH-benzo[b][l,4]diazepine (1) was synthesized by AgNO3-catalyzed reaction of o-phenylenediamine with excess of acetone. Coupling of benzodiazepine 1 with 4-chloroaniline afforded intermediate benzodiazepine 2 which was subsequently reacted with benzaldehyde derivatives via microwave irradiation technique to access twelve final targeted benzodiazepine Schiff bases, 3a-l. The chemical structures of the scaffolds 3a-l were authenticated using analytical and spectroscopic data. Benzodiazepine Schiff bases 3a-l were investigated for their in vitro antimicrobial activities using Agar diffusion technique and screened for their minimum inhibitory concentration (MIC) using microtube dilution technique. Ten pathogenic organisms comprising of seven bacterial and three fungal isolates were utilized for the screening. Ciprofloxacin was the positive control for antibacterial screening while fluconazole was engaged as the positive control for the antifungal screening. The most efficacious antimicrobial agent among the series was (E)-l-(2-Chloropheny1)-N-(4-(2,2,4-trimethyl-2,3-dihydro-lH-benzo[b][l,4] diazepinlyl)phenyl)methanimi ne (3b) with a MIC value of 3.13 µg/mL and MBC of 6.25 µg/mL among all the synthesized compounds synthesized and screening for antimicrobial assessment. Compound 3b also emerged as the best anti-tubercular agent IC50 of 40 µg/mL against Mycobacterium tuberculosis, Mycobacterium bovis and H37Rv